Multiple Bone Hemangiomas Presenting As Bony Metastasis of Unknown Primary - Daoud, Ehab (Journal of Medicine, 2010)
Bone hemangiomas are rare benign tumors of the bones of vascular origin. A patient with bony pains and abnormal radiological findings is described. Following an unsuccessful extensive search for primary malignancy the patient was diagnosed as multiple bone hemangioma. This case serves as a reminder for considering benign causes of bone lesion while investigating cases with such presentation. Keywords: Hemangioma; multiple; sclerosing hemangioma; back pain DOI: 10.3329/jom.v11i2.5473 J MEDICINE 2010; 11 : 196-199